KESIAPAN EKSPOR UNTUK PRODUK MAKANAN DARI DESA WALURAN MANDIRI CILETUH-PALABUHANRATU UNESCO GLOBAL GEOPARK SUKABUMI - Bambang Darmawan; Hizba Muhammad Sadida; Aulia Zikri Rahman; Hanissa Okitasari; Vina Dwiyanti (Lentera Karya Edukasi, 2022)
This Community Service activity is motivated by the limitations of the target audience in implementing product marketing strategies. The pandemic situation also affects the ratio of tourists visiting the Ciletuh area which directly affects the level of product sales marketed by business actors so that alternative strategies are needed in marketing products. The method of implementing this training activity includes the stages of analyzing the needs of residents in carrying out business activities, planning appropriate training models and media related to the insight of exporters' activities during the pandemic and post-pandemic, implementing activities, then in the final stage monitoring the program and evaluating the service activities of In the implementation of this service activity, there is enthusiasm from the community of waluran independent village SMEs to carry out export activities, but the understanding of exports is still quite minimal. The result of the training activities is an increase in people's knowledge of export products. The surrounding community is still in selling their daily products